TWO SPECIES OF Galeopsomyia (HYMENOPTERA, EULOPHIDAE) FROM BRAZIL: A CORRECTION OF PUBLISHED MISTAKES - Perioto, Nelson Wanderley; Costa, Valmir Antonio; Lara, RogÃ©ria InÃªs Rosa (REVISTA DE AGRICULTURA, 2016)
TWO SPECIES OF Galeopsomyia (HYMENOPTERA, EULOPHIDAE) FROM BRAZIL: A CORRECTION OF PUBLISHED MISTAKES